Deliverability of Gas condensate "sandstone reservoir"Khabour Fm. Akkas Field,western Iraq - AL- Hadidy, Dr. Aboosh. H. (Journal of Petroleum Research and Studies, 2011)
The Khabour Fm. (ordovicain) presents a prospective target for exploration and developiment, as it certains "Gas Condensate" light gravity, low sulfur oil, and sweet gas as proven by Akkas field, in the western desert of Iraq . Gas- condensate project is in depth,hot,low permeability reservoir in the upper K1,K3,K5 sandstone members ,it’s well known that the deliverability of gas-condensate wells can be improved by the formation of acondensate bank once a bottomhole pressure drope below the dewpoint. Improving deliverability can be improved by use the techniques as,Fracturing andchemical treatment. The Khabour formation total thickness is 1913m,represntaed by elastic series mainly shaly intercalated with sandstone beds in the lower part and by well developed sandstone beds in the upper part, In Akk-1 which is subdivided into eight members according to sand /shale ratio, the need for accurate estimate for reservoir properties of these member extends to the whole life cycle of a reservoir; detailed simulation and planning of future production which including for discovery , appraisal , planning , development and production from Akkas field.